Antioxidant, lipid peroxidation inhibitory activities, and hepatoprotective effect of extracts of Phyllanthus emblica L. fruits - Manh Cuong, Nguyen; Ngoc Khanh, Pham; Thu Huong, Tran; Thi Ha, Vu; Ngoc Anh, Hoang Thi; Thi Thao, Do; Thi Cuc, Nguyen; Dao Cuong, To (Vietnam Journal of Science and Technology, 2022)
Phyllanthus emblica L., commonly known by Vietnamese people as “Me rừng” or “Me mận”, is widely distributed in Viet Nam and has been used in folk medicines for treatment of numerous ailments. The preparation of P. emblica fruit extracts in different solvent types have significant effects on extraction efficiency, phytochemical profile, and biological activity. This study aims to investigate the effects of six different solvents (methanol, ethyl acetate, water, 50 %, 70 %, and 96 % ethanol) used in the production of the corresponding extracts, denoted PE-M, PE-EA, PE-W, PE-50Et, PE-70Et, and PE-96Et, respectively) on phytochemical yield, in vitro antioxidant capacity, ex vivo lipid peroxidative inhibitory activity, and hepatoprotective potential of P. emblica fruits collected in Viet Nam. Our results showed that the PE-M and PE-96Et extracts of P. emblica fruits possessed the highest total phenolic content (321.6 and 287.9 GAE mg/g, respectively). However, because of its low toxicity, PE-96Et turned into the best potential candidate with DPPH antioxidant capacity (SC50 of 4.17 µg/mL), lipid peroxidative inhibitory activity via MDA assay (IC50 of 3.54 µg/mL), and hepatoprotective activity on CCl4 intoxicated liver platform (PC50 of 56.6 µg/mL). The HPLC-MS profiles of the PE-M and the PE-96Et extracts showed the presence of mucic acid 3-O-gallate (1), mucic acid 2-O-gallate (2), mucic acid 1,4-lactone 3-O-gallate (3), glucogallin (4), mucic acid 1,4-lactone 2-O-gallate (5), gallic acid  (6), mucic acid dimethyl ester 3-O-gallate (7), mucic acid 1,4-lactone 1-ethyl ester 2-O-gallate (8), and quercetin (9). The results indicated that the 96 % ethanol extract of P. emblica fruits is highly potential for further investigation and development of hepatoprotective products.